Integrating comprehensive geriatric assessment into digital dentistry - Antonius Edwin Sutikno; Didin Mirandani; Hutomo Setia Budi; Evan Raditya Pratomo; Aurelia Felisha Lukwanto; Clara Suryani Awengkari; Felicia Natalie Purnomo; Tiffany Grace Siamena (Indonesian Journal of Dental Medicine, 2026)
Background: Aging population is rapidly increasing worldwide and is associated with higher prevalence of multimorbidity, frailty, and functional decline. Oral health problems such as tooth loss, periodontal disease, and reduced masticatory function frequently occur in geriatric populations and may negatively affect nutritional status and overall quality of life. Comprehensive Geriatric Assessment (CGA) enables multidimensional evaluation of older adults; however, its integration into digital dentistry to support preventive-promotive oral care remains limited. Developing a digital system that considers the functional variability of geriatric patients may improve accessibility and personalization of dental care. Purpose: To examine a geriatric assessment instrument and develop a risk-stratified digital dentistry model grounded in functional profiling. Methods: An exploratory study was conducted involving 30 geriatric patients (≥60 years) attending a public hospital dental clinic. Validity was assessed using Pearson product-moment correlation, and reliability was evaluated using Cronbach’s alpha. Focus Group Discussions (FGDs) were conducted to refine the conceptual digital framework. Results: After eliminating invalid items, 13 indicators met validity criteria (r>0.3) and demonstrated high reliability (α= 0.889). Most participants were independent in basic Activities of Daily Living (ADL), whereas dependency was more evident in Instrumental Activities of Daily Living (IADL), particularly in financial (60%) and medication management (36.7%). FGD findings emphasized the need for simplified user interfaces, caregiver-linked monitoring systems, and preventive-focused educational features. Conclusion: Validated CGA parameters can support the development of a risk-based digital dentistry system. Functional stratification may enhance the personalization and accessibility of preventive oral healthcare for geriatric populations.